Preparation and properties research of spunlaced cellulose acetate/polylactic acid mask base cloth. Issue 11 (26th October 2022) - Zhang, Shujie; Zhang, Ziwei; Fu, Lisong; Wang, Rui
Abstract: In view of the situation, mask base cloth can't be degraded naturally and there is rapid development of green fiber, cellulose acetate (CA) and polylactic acid (PLA) were used to prepare spunlaced mask base cloth to solve the problems of high energy consumption and non-recycling during producing. Mechanical property, air permeability, moisture permeability, softness, micro structure characterization and water absorption were studied and analyzed. Taking air permeability and flexural rigidity as target values, spunlaced CA/PLA base cloth was optimized by orthogonal test. The results show that when surface density is 60 g/m 2, thickness less than 1.2 mm, and blending ratio of CA to PLA = 50:50, the air permeability is the best; when CA to PLA is 25:75, the flexural rigidity is the worst.